2004
DOI: 10.1542/peds.113.1.e7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokine Profile in Children With Severe Acute Respiratory Syndrome

Abstract: ABSTRACT. Objective. To study the inflammatory cytokine profile in children with severe acute respiratory syndrome (SARS) and to investigate whether monoclonal antibody to tumor necrosis factor-␣ (TNF-␣) could be considered for treatment of these patients.Methods. Plasma inflammatory cytokine concentrations (interleukin [IL]-1␤, IL-6, IL-8, IL-10, IL-12p70, and TNF-␣) were monitored longitudinally on admission, immediately before corticosteroids, and 1 to 2 days and 7 to 10 days after the drug treatment in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 20 publications
(33 reference statements)
4
67
1
1
Order By: Relevance
“…Zhang et al [87] reported a fall in IL-8 levels, whereas Wang et al [89] reported no change in levels. Similarly, Ng et al [90] and Wang et al [89] reported no change in IL-6 levels. With TNF-α, the picture is very mixed, with several reports stating an increase in levels [77,86,89], some reporting no significant elevation [83,87,90] and others reporting a fall in levels [85].…”
Section: Pathogenesismentioning
confidence: 88%
“…Zhang et al [87] reported a fall in IL-8 levels, whereas Wang et al [89] reported no change in levels. Similarly, Ng et al [90] and Wang et al [89] reported no change in IL-6 levels. With TNF-α, the picture is very mixed, with several reports stating an increase in levels [77,86,89], some reporting no significant elevation [83,87,90] and others reporting a fall in levels [85].…”
Section: Pathogenesismentioning
confidence: 88%
“…Although a recent report suggests that young infants with SARS could become ill and require supplemental oxygen [26], young children, in general, develop a milder form of disease with a less aggressive clinical course than that of teenage and adult patients [6][7][8]. The understanding of the genome sequence of the SARS-CoV [27][28][29][30], the immunological profiles [15], and the natural history of the disease in different age groups [6-8, 12, 24] may hopefully facilitate the development of rapid and accurate diagnostic tests, treatments and vaccines to fight against this highly contagious and potentially devastating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Whether children with mild or moderate SARS should be subjected to such potentially toxic treatment requires to be tested by future randomised clinical trials. Our latest study on cytokines does not support the use of TNF· monoclonal antibody for treatment of this category of patients [15]. New antiviral agents and immunomodulating drugs, such as kaletra and interferon-1ß, are currently under investigation.…”
Section: Managementmentioning
confidence: 97%
See 1 more Smart Citation
“…1 In brief, case 3 was the only patient who did not receive corticosteroid treatment. Cases 2 and 6 required pulse methylprednisolone, and case 6 also received intravenous ribavirin.…”
Section: Methodsmentioning
confidence: 99%